Optimization of response surface methodology (RSM) for defluorination of spent carbon cathode (SCC) in fire-roasting aluminum electrolysis. (31st May 2022) - Zhu, Zhi; Xu, Lei; Han, Zhaohui; Liu, Jianhua; Zhang, Libo; Tian, Shihong; Xu, Yongchao; Koppala, Sivasankar
Highlights: Response surface methodology can effectively remove fluoride from SCC. Determine the optimal treatment process in a conventional muffle furnace. When the roasting temperature is 1499 °C, the treatment time is 3.33 h, and the average particle size is 10 mm, the fluorine removal rate reaches 88%. Abstract: Spent carbon cathode (SCC) is a typical toxic and hazardous solid waste generated in aluminum electrolysis. The harmless treatment of SCC is extremely important for the aluminum electrolysis industry. Herein, the response surface methodology was used to investigate the best process for removing fluoride from the SCC of aluminum electrolysis using the roasting method. A Box–Behnken design (BBD) was used to investigate the effects of three independent variables, namely, particle size, roasting temperature, and treatment time, on the fluorine removal rate of the SCC. Seventeen groups of experiments were conducted according to these three factors. Statistical analysis system software and a second-order polynomial model were used to analyze the data and predict the response. The results showed that the particle size, roasting temperature, and treatment time significantly influenced fluoride removal in the SCC. Under optimum process conditions, the system predicted a fluoride removal rate of 87% for the SCC. Validation experiments were conducted on the fluoride removal rate of the SCC under optimum process conditions. The results showed that the actual value reached 88%. The X-ray diffraction analysis before and after calcination showed that a small amount of SiO2 was converted into SiC through a carbon thermal reduction reaction after calcination. This paper provides a theoretical basis for the best process of roasting SCC to remove fluoride. It also has a certain guiding significance for other solid waste treatments.